"I don't think you belong in here:" The impact of gender segregated bathrooms on the safety, health, and equality of transgender people. Issue 1 (2nd January 2022) - McGuire, Jenifer K.; Okrey Anderson, Sloan; Michaels, Cari
Abstract: The current study presents reflections from transgender youth regarding experiences with toilet access, both in isolated gender-neutral facilities and standard gender segregated facilities in North America. Transgender youth experience barriers to bathroom access that can contribute to negative mental health outcomes, impede educational functioning, and threaten physical safety. Recommendations are made for gender inclusive designs that diminish the isolation of gender-neutral designs and preempt the backlash inherent in existing gender segregated practices. Gender inclusive bathrooms, in addition to the benefits to transgender people, could also contribute to better quality of life for parents of small children, people with disabilities and their caregivers, and other marginalized individuals.